Pendampingan dan Bimbingan Teknis Akuntansi Persediaan Sesuai PSAK 202 Bagi Guru MGMP Akuntansi Sumatera Barat - Ferdawati, Ferdawati; Siskawati, Eka; Gustati, Gustati; Sulastri, Reni Endang; Haykal, Muhammad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service activity aims to improve the understanding and skills of accounting teachers in implementing the latest PSAK 202 standards. This activity was carried out on June 27, 2024 at the secretariat of the West Sumatra Accounting MGMP. The main focus of this activity is on inventory valuation methods, including FIFO, LIFO, and Average Cost, and their impact on financial statements. This activity was carried out in two sessions, namely the presentation session and interactive discussion. This activity involved collaboration between the West Sumatra Accounting MGMP and the community service team from the Padang State Polytechnic. The results of the service showed a significant increase in the conceptual understanding of teachers, as reflected in their responses in the questionnaire evaluation. This mentoring successfully facilitated increased knowledge and adaptation of teaching practices in accordance with applicable financial accounting standards